On the 400th anniversary of the birth of Thomas Willis - Molnár, Zoltán (Brain, 2021)
Zoltan Molnar marks the 400th anniversary of the birth of one of the great neuroanatomists, Thomas Willis. While Willis’ name is usually associated with ‘the circle’ and the word ‘neurologia’, his work also formed the foundation of modern translational research and clinical medicine.